EFFECTIVE STRATEGIES FOR PREVENTING BRIBERY ON VILLAGE FUND MANAGEMENT IN PANDEGLANG REGENCY - Bambang Arianto; Rahmad Bakthiar (Assets: Jurnal Akuntansi dan Pendidikan, 2023)
ABSTRACTThis study aims to elaborate an effective strategy for preventing bribery in managing Village Funds in Pandeglang Regency. The method of bribery in managing the Village Fund occurs when the bribe giver provides remuneration to the Village Government apparatus and manages village finances. The results of the study indicate that the practice of bribery in the management of village funds still needs to be discovered, so prevention is needed. This study uses an explanatory qualitative approach with in-depth interviews with five village heads in Pandeglang Regency. This study states that the competence of human resources of Village Government officials is the main obstacle to strengthening internal control. This study also says that supporting integrity, transparency, and accountability for Village Government officials is an effective strategy for managing Village Funds in Pandeglang Regency, Banten.ABSTRAKPenelitian ini bertujuan mengelaborasi strategi efektif bagi upaya pencegahan praktik suap pada pengelolaan Dana Desa di Kabupaten Pandeglang. Praktik suap dalam pengelolaan Dana Desa terjadi saat pemberi suap memberikan balas jasa kepada aparatur Pemerintahan Desa yang mengelola keuangan desa. Hasil penelitian menunjukkan bahwa praktik suap dalam pengelolaan Dana Desa masih sulit untuk terdeteksi sehingga diperlukan pencegahan. Penelitian ini menggunakan pendekatan kualitatif eksplanatoris dengan teknik wawancara mendalam terhadap lima Kepala Desa di Kabupaten Pandeglang. Penelitian ini menyatakan bahwa kompetensi sumber daya manusia para aparatur Pemerintahan Desa menjadi kendala utama dalam penguatan pengendalian internal. Penelitian ini juga menyatakan bahwa penguatan aspek integritas, transparansi dan akuntabilitas bagi para aparatur Pemerintahan Desa menjadi strategi efektif bagi pengelolaan Dana Desa di Kabupaten Pandeglang, Banten.